COMPARISON OF EXPERIMENTAL RESPONSE SURFACE METHODOLOGY AND COMPUTATIONAL FLUID DYNAMICS STUDIES IN 6063 ALUMINIUM ALLOY THERMOSYPHON USING IRON (II, III) OXIDE NANOFLUID - ALAGAPPAN, N.; ALAGAPPAN, N.; KARUNAKARAN, N. (International Journal of Psychosocial Rehabilitation, 2020)
This study presents a comparison of the results obtained from experiments response surface methodology(RSM) and computational fluid dynamics (CFD) of the 6063 aluminium alloy two phase closed thermosyphon (TPCT) using Iron (II, III) oxide(Fe3O4) water based nano fluid. A 17 set of experimental reading were taken by response surface methodology. The input responses are heat input, angle of orientation and flow rate of water in condenser section of TPCT. The output response to be compared with RSM and CFD is thermal resistance (Rth). The data derived from experimental were validated by CFD using Volume of fluid (VOF) model. A reasonable good agreement was obtained between the results of the experimental RSM and CFD.